Identification and Functional Characterization of Sugarcane Invertase Inhibitor (ShINH1): A Potential Candidate for Reducing Pre- and Post-harvest Loss of Sucrose in Sugarcane - Shivalingamurthy, Suresha G.; Anangi, Raveendra; Kalaipandian, Sundaravelpandian; Glassop, Donna; King, Glenn F.; Rae, Anne L. (Frontiers in Plant Science, 2018)
In sugarcane, invertase enzymes play a key role in sucrose accumulation and are also involved in futile reactions where sucrose is continuously degraded during the pre- and post-harvest period, thereby reducing sugar yield and recovery. Invertase inhibitor (INVINH) proteins play a key role in post-translation regulation of plant invertases through which sucrose hydrolysis is controlled. INVINH proteins are small (18 kDa) members of the pectin methylesterase inhibitor superfamily and they are moderately conserved across plants. In the present study, we identified two INVINH genes from sugarcane, ShINH1 and ShINH2. In silico characterization of the encoded proteins revealed 43% sequence identity at the amino acid level, confirming the non-allelic nature of the proteins. The presence of putative signal peptide and subcellular targeting sequences revealed that ShINH1 and ShINH2 likely have apoplasmic and vacuolar localization, respectively. Experimental visualization of ShINH1–GFP revealed that ShINHI is indeed exported to the apoplast. Differential tissue-specific and developmental expression of ShINH1 between leaf, stalk, flower and root suggest that it plays a role in controlling source-sink metabolic regulation during sucrose accumulation in sugarcane. ShINH1is expressed at relatively high levels in leaves and stalk compared to flowers and roots, and expression decreases significantly towards internodal maturity during stalk development. ShINH1is expressed at variable levels in flowers with no specific association to floral maturity. Production of recombinant ShINH1 enabled experimental validation of protein function under invitro conditions. Recombinant ShINH1 potently inhibited acid invertase (IC50 22.5nM), making it a candidate for controlling pre- and post-harvest deterioration of sucrose in sugarcane. Our results indicate that ShINH1 and ShINH2 are likely to play regulatory role in sucrose accumulation and contribute to the improvement of sugar yield and recovery in sugarcane.